Optical investigation of palladium(II) phthalocyanine including an aromatic group - Ozcesmeci̇, İbrahim; Sorar, İdris (The Turkish Chemical Society, 2018)
Peripherally β-naphthoxy unit substituted palladium(II) phthalocyanine was synthesized from corresponding phthalonitrile compounds. The palladium (II) phthalocyanine was characterized with ultraviolet–visible spectroscopy (UV-Vis), fourier transform- infrared spectroscopy (FT-IR), mass and elemental analyses techniques. Thin films of palladium (II) phthalocyanine were prepared using different organic solvents by spin coating technique. Transmittance and absorbance spectra of the thin films were studied in the wavelength range of 200–1000 nm. Optical band gaps of palladium (II) phthalocyanine thin films were also calculated.
Keywords: ?-naphthol; Engineering; Phthalocyanine; β-naphthol; palladium; thin film; optical properties; Optical properties; Mühendislik; Phthalocyanine; Thin film; Chemical Engineering; Kimya Mühendisliği; Palladium